2010
DOI: 10.1186/1476-4598-9-140
|View full text |Cite
|
Sign up to set email alerts
|

Targeting melanoma growth and viability reveals dualistic functionality of the phosphonothionate analogue of carba cyclic phosphatidic acid

Abstract: BackgroundAlthough the incidence of melanoma in the U.S. is rising faster than any other cancer, the FDA-approved chemotherapies lack efficacy for advanced disease, which results in poor overall survival. Lysophosphatidic acid (LPA), autotaxin (ATX), the enzyme that produces LPA, and the LPA receptors represent an emerging group of therapeutic targets in cancer, although it is not known which of these is most effective.ResultsHerein we demonstrate that thio-ccPA 18:1, a stabilized phosphonothionate analogue of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
46
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(46 citation statements)
references
References 46 publications
0
46
0
Order By: Relevance
“…OVCAR-3, SKOV-3, or HeyA8 cells were examined for viability as previously described (14,20) using CellTiter Blue reagent (Promega). In cisplatin and paclitaxel treatment experiments, the cells were treated with chemotherapy after 24 hours of transfection.…”
Section: Cell Viabilitymentioning
confidence: 99%
See 2 more Smart Citations
“…OVCAR-3, SKOV-3, or HeyA8 cells were examined for viability as previously described (14,20) using CellTiter Blue reagent (Promega). In cisplatin and paclitaxel treatment experiments, the cells were treated with chemotherapy after 24 hours of transfection.…”
Section: Cell Viabilitymentioning
confidence: 99%
“…siRNA knockdown of LPA receptors SKOV-3 cells were transfected with Dharmacon SMART pools of siRNA reagents (ThermoScientific/Dharmacon, Inc.) targeting the individual LPA receptors as previously described (14) using Dharmafect reagent (ThermoScientific/Dharmacon) and following the protocol provided by the manufacturer.…”
Section: Materials and Reagentsmentioning
confidence: 99%
See 1 more Smart Citation
“…This enzyme, autotaxin (ATX), was first isolated from the conditioned medium of melanoma cells and was thought to be responsible for melanoma cell motility (Stracke, Krutzsch et al 1992). Recent studies have shown that targeting either the LPA3 receptor or ATX effectively reduces melanoma cell viability (Altman et al 2010). Furthermore, research devoted to producing inhibitors and antagonists targeting the ATX-LPA receptor axis has yielded a large variety of compounds (Albers, Dong et al 2010;Altman et al 2010;Baker, Fujiwara et al 2006;Block, Duff et al 2010;Hoeglund, Bostic et al 2010;North, Howard et al 2010;Xu, Yang et al 2009), suggesting the critical role of this pathway in cancer.…”
mentioning
confidence: 99%
“…Interestingly, the lysophospholipase D that is responsible for the vas t m a j o r i t y o f t h e production of LPA from lysophosphatidylcholine is also expressed extracellularly and is a major target in melanoma (Altman et al 2010;Liu, Murph et al 2009). This enzyme, autotaxin (ATX), was first isolated from the conditioned medium of melanoma cells and was thought to be responsible for melanoma cell motility (Stracke, Krutzsch et al 1992).…”
mentioning
confidence: 99%